Phương pháp viễn thám nhiệt trong nghiên cứu phân bố nhiệt độ bề mặt đô thị - Vân, Trần Thị; Lan, Hoàng Thái; Trung, Lê Văn (Vietnam Journal of Earth Sciences, 2009)
Thermal remote sensing method in study on urban surface temperature distribution ...